2022
DOI: 10.3389/fgene.2022.874805
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Characteristics in TP53-Mutant Hepatocellular Carcinoma Using Bioinformatics

Abstract: Background: TP53 mutations are the most frequent mutations in hepatocellular carcinoma (HCC) and affect the occurrence and development of this cancer type. Therefore, it is essential to clarify the function and mechanism of TP53 mutations in HCC.Methods: We performed a sequence of bioinformatic analyses to elucidate the characteristics of TP53 mutations in HCC. We downloaded the data of hepatocellular carcinoma from The Cancer Genome Atlas database and used different R packages for serial analyses, including g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
3
5
0
Order By: Relevance
“…We also ranked TP53 expression from low to high so the LOCC graph will show a significant HR above 1, reducing overlapping lines and making it easier to read the graph (Fig 3D). Therefore, both expression and mutation of TP53 can be used in combination to help determine the prognosis of patients with LIHC, which is in line with previous studies (16,17).…”
Section: Low Expression and Mutations Of Tp53 Are Associated With A P...supporting
confidence: 82%
“…We also ranked TP53 expression from low to high so the LOCC graph will show a significant HR above 1, reducing overlapping lines and making it easier to read the graph (Fig 3D). Therefore, both expression and mutation of TP53 can be used in combination to help determine the prognosis of patients with LIHC, which is in line with previous studies (16,17).…”
Section: Low Expression and Mutations Of Tp53 Are Associated With A P...supporting
confidence: 82%
“… Zhang et al (2021) found two directly regulated lncRNA associated with TP53 mutations in HCC. These studies provide new insights into personalized prediction methods, but the average frequency of TP53 mutations in HCC is about 30% ( Yang et al, 2022 ). The prognostic model for patients with TP53 wild-type HCC is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In PubMed and other databases, we found that there was a lack of CDRT15 studies. [25,26] We analyzed the correlation between expression levels of CDRT15 and 24 types of immune cell infiltration in CCA, and the result showed that the CDRT15 expression was negatively correlated with the Treg, DCs, and Cytotoxic cells. We considered that CDRT15 may be involved in the immune infiltration process of CCA and play a certain role.…”
Section: Discussionmentioning
confidence: 99%